The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/cjce.20640
|View full text |Cite
|
Sign up to set email alerts
|

Successive linearisation analysis of unsteady heat and mass transfer from a stretching surface embedded in a porous medium with suction/injection and thermal radiation effects

Abstract: In this study, we investigate the application of the new successive linearisation method (SLM) to the problem of unsteady heat and mass transfer from a stretching surface embedded in a porous medium with suction/injection and thermal radiation effects. The governing nonlinear momentum, energy and mass transfer equations are successfully solved numerically using the SLM approach coupled with the spectral collocation method for iteratively solving the governing linearised equations. Comparison of the SLM results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 43 publications
3
9
0
Order By: Relevance
“…where D = ((2/ )D) and D is the Chebyshev spectral differentiation matrix (see, e.g., [20,21]). Substituting (17)- (19) in (13) results in the matrix equation…”
Section: Successive Linearisation Methods (Slm) Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…where D = ((2/ )D) and D is the Chebyshev spectral differentiation matrix (see, e.g., [20,21]). Substituting (17)- (19) in (13) results in the matrix equation…”
Section: Successive Linearisation Methods (Slm) Approachmentioning
confidence: 99%
“…Several approximation techniques have been developed to tackle this problem such as the homotopy analysis method [9][10][11], homotopy perturbation method [12,13], spectral homotopy analysis method [14,15], and variational iteration method [16]. In this paper, we employ the successive linearisation method [17][18][19] to tackle a fourth order nonlinear boundary value problem that governs the squeezing flow problem between parallel plates. In this work, we assess the applicability of the SLM approach in solving nonlinear problems with bifurcations.…”
Section: Introductionmentioning
confidence: 99%
“…Upon these imports, Vyas and Srivastava [16] investigated the radiation effects on the MHD flow over a non-isothermal stretching sheet in a porous medium. Motsa and Shateyi [17] studied the problem of unsteady heat and mass transfer from a stretching surface embedded in a porous medium with suction/injection and thermal radiation effects using successive linearization method, and showed that the results obtained are more accurate and efficient than those obtained by the homotopy method and Runge-Kutta numerical scheme. Vyas and Srivastava [18] studied the radiation effects on MHD boundary layer flow in a porous medium over a non-isothermal stretching sheet in presence of dissipation.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years Motsa and his coworkers [15][16][17][18] have developed successful methods based on the spectral method to solve nonlinear similarity boundary layer problems. The methods include, among others, the spectral relaxation method (SRM) [15,19,20], the spectral successive linearisation method [21][22][23], spectral homotopy analysis method [24][25][26][27], and the spectral quasilinearisation method (SQLM) [16]. The SRM is based on simple decoupling and rearrangement of the governing equations and numerically integrating the resulting equations using the Chebyshev spectral collocation method.…”
Section: Introductionmentioning
confidence: 99%